Review on foundation practices for expansive soils, special emphasis on granular anchor pile foundation - RaviTeja, Munnangi; R Krishna Murthy, N (International Journal of Engineering and Technology, 2018)
Mostly the lightly loaded structures founded in expansive soils develop cracks owing to alternate shrinkage and swelling as the weight of superstructure cannot counteract the swelling pressure. Hence the cost of foundation to be laid in these soils must be suitable proportions to low cost of structure. This paper presents a critical review on emphasis on granular anchor pile foundation andÂ other the foundation practices for expansive soil.Â